Lymphoepithelioma-like carcinoma of the breast: a case report and review of the literature - Fadila, Kouhen (Pan Afr Med J, 2019)
Lymphoepithelioma-like carcinoma of the breast is uncommon with only 21 patients documented in the literature. It can wrongly be diagnosed as medullary carcinoma and certain types of lymphoma due to undifferentiated proliferation of malignant epithelial cells with prominent lymphoid infiltration. In this paper, we present a case of LELC of the breast in a 64-year-old female with breast LELC and a discussion based on a review of the literature.